2009
DOI: 10.3382/ps.2008-00562
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diets containing different concentrations of mannanoligosaccharide or antibiotics on growth performance, intestinal development, cecal and litter microbial populations, and carcass parameters of broilers

Abstract: The effects of 2 levels of mannanoligosaccharide (MOS) in feed were compared with antibiotic growth promoters on growth performance, intestinal morphology, cecal and litter microbial populations, and carcass parameters in broilers raised in a sanitary environment. Dietary treatments included: 1) antibiotic growth promoter-free diet (control), 2) VIRG (diet 1 + 16.5 mg/kg of virginiamycin), 3) BACT (diet 1 + 55 mg/kg of bacitracin), 4) LMOS (diet 1 + 0.2% MOS), and 5) HMOS (diet 1 + 0.5% MOS). Birds were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
147
2
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 236 publications
(172 citation statements)
references
References 36 publications
15
147
2
8
Order By: Relevance
“…Apparently, rapid increases in villous height and surface area occur at different rates in chick intestinal segments, reaching a plateau at 6 to 8 days in the duodenum and after 10 days in the jejunum and ileum (Uni et al, 1996). Long villi are correlated with improved gut health, and an increase in duodenal and jejuna height or length (Baurhoo et al, 2009). Thus, birds whose GIT were stimulated earlier in life show better response to growth performance and nutrient utilisation efficiency.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Apparently, rapid increases in villous height and surface area occur at different rates in chick intestinal segments, reaching a plateau at 6 to 8 days in the duodenum and after 10 days in the jejunum and ileum (Uni et al, 1996). Long villi are correlated with improved gut health, and an increase in duodenal and jejuna height or length (Baurhoo et al, 2009). Thus, birds whose GIT were stimulated earlier in life show better response to growth performance and nutrient utilisation efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…As reported by Paul et al (2007), the increase of villous height of various small intestine segments may be attributed to the role of the intestinal epithelium as a natural barrier to pathogenic bacteria and toxic substances that are present in the intestinal lumen. Furthermore, M. oleifera leaves contain short-chain carbohydrates, glycosides, which are reported to cause major increases in the height of the jejuna villi compared with AGP and AGP-free diets (Baurhoo et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…level in slaughter pigs has to our knowledge not previously been reported, but feeding of chicks with fructooligosaccharides has been shown to reduce the colonization with C. jejuni (Schoeni and Wong, 1994). Similarly, Baurhoo et al (2009) showed that the Campylobacter counts in broilers were reduced at day 34 after dietary inclusion of mannaoligosaccharide (MOS), although not at day 14 or 24.…”
Section: Discussionmentioning
confidence: 99%